Understanding the cataract treatment disparities among older adults in India - Singh, Rajeev Ranjan; Mohanty, Sanjay K. (Frontiers in Public Health, 2024)
Background Cataract is a leading cause of global blindness, affecting around 33% of blind individuals worldwide. It significantly impacts individuals’ well-being, independence, and quality of life, posing a substantial economic burden. India’s rapidly ageing population necessitates an examination of cataract prevalence and treatment disparities. No attempts have been made to address socioeconomic variation in treatment disparities of effective cataract treatment coverage among older adults in India. Data and method This study utilises data from the Longitudinal Ageing Study of India (LASI) conducted in 2017–18, that covered, 73,396 individuals aged 45 and above. Logistic regression, univariate, and bivariate analyses were employed to understand the variation of cataract and their associations with various demographic factors. Visual acuity tests and self-reported cataract data were used. Results The prevalence of cataract among older adults in India was 14.25%, with higher rates among females and the older adult. Socioeconomic disparities werelarge, with lower prevalence among those with higher education and urban residence. Despite the effectiveness of cataract surgery, disparities in treatment access and effective coverage persisted. Approximately 27.52% of older adults did not receive cataract treatment, and those who received out of them 28% did not receive effective treatment. The effective treatment was lower among female, less educated, and poor. Conclusion Cataract remains a significant public health concern in India, particularly among older adults. The study highlights the importance of addressing socioeconomic disparities in cataract treatment access and quality of care. Targeted interventions are needed to bridge these gaps, ultimately improving visual health outcomes and well-being among older adults in India.